A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Changes in cloudiness over the Amazon rainforests during the last two decades: diagnostic and potential causes - Paola A. Arias; Rong Fu; Carlos D. Hoyos; Wenhong Li; Liming Zhou (Climate Dynamics, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Differentiation of Fecal Escherichia coli from Human, Livestock, and Poultry Sources by rep-PCR DNA Fingerprinting on the Shellfish Culture Area of East China Sea - Hong-Jia Ma; Ling-Lin Fu; Jian-Rong Li (Current Microbiology, 2011)